2021
DOI: 10.1002/jee.20392
|View full text |Cite
|
Sign up to set email alerts
|

Constructive alignment between holistic competency development and assessment in Hong Kong engineering education

Abstract: Background: Holistic competencies comprise various holistic skills (e.g., communication) and positive values and attitudes (e.g., empathy). There have been increasing efforts worldwide to foster students' holistic competency development within engineering curricula. While recent studies indicate a positive shift, it remains unclear whether such efforts are driven by only a handful of individuals or more widely supported by systemic changes to constructively align competency development with the engineering cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 52 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Landry, et al explored the teaching quality assessment model for pre-school education and concluded that the assessment model has a positive impact on the improvement of teaching quality level and the reform of teaching mode [15]. Chan, C. K. Y. et al carried out a project study on engineering teaching in Hong Kong, and analyzed and summarized the study to emphasize the necessity of practical education and professional knowledge training for engineering educators and combined with teaching quality assessment to improve the teaching standard and professionalism of engineering teachers [16].…”
Section: Introductionmentioning
confidence: 99%
“…Landry, et al explored the teaching quality assessment model for pre-school education and concluded that the assessment model has a positive impact on the improvement of teaching quality level and the reform of teaching mode [15]. Chan, C. K. Y. et al carried out a project study on engineering teaching in Hong Kong, and analyzed and summarized the study to emphasize the necessity of practical education and professional knowledge training for engineering educators and combined with teaching quality assessment to improve the teaching standard and professionalism of engineering teachers [16].…”
Section: Introductionmentioning
confidence: 99%
“…Various network platforms have been widely used in college English teaching, initially constructing online and offline blended classrooms, aiming at cultivating students' English proficiency, breaking down the barriers of disciplinary specialties, and breaking through the limitations of classroom teaching to extend the classroom learning space beyond the classroom [4][5]. In our university English teaching, teachers put the overall development of students in an important position, not only cultivating students' ability to tell China's story in English but also helping them to master the values, moral norms, and codes of conduct of the era and society in which they live, so as to achieve the mutual identification of the individual with the era and the individual with the society [6].…”
Section: Introductionmentioning
confidence: 99%
“…Lasrado and Kaul (2021) used constructive alignment in a business and quality management course to introduce innovative ways of designing authentic tasks and aligning them with subject learning outcomes. Chan and Lee (2021) utilized constructive alignment to assess holistic attributes in Hong Kong's engineering education, revealing a reliance on indirect assessment methods. Their study emphasized the difficulty of transitioning to direct assessments without well-designed, standardized marking rubrics.…”
mentioning
confidence: 99%
“…Their study emphasized the difficulty of transitioning to direct assessments without well-designed, standardized marking rubrics. Caution is warranted when applying Chan and Lee's (2021) findings to institutions with different characteristics; instructors must consider the unique features of each educational context. From prior research, it can be inferred that implementing a more robust constructive alignment approach is associated with enhanced student learning experiences, demonstrating adaptability across various course contexts.…”
mentioning
confidence: 99%